PENGARUH KEADILAN, TARIF PAJAK, TEKNOLOGI DAN INFORMASI, DISKRIMINASI, DAN SISTEM PERPAJAKAN TERHADAP PENGGELAPAN PAJAK (Studi Kasus Pada WPOP Pedagang Eceran di KPP Pratama Rengat) - Gusmella Ismarita; Zirman Zirman; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine the effects of justice, tax rates, technology and information, discrimination, and taxation system against tax evasion in KPP Pratama Rengat.This research was conducted on taxpayers of individuals registered in KPP Pratama Rengat. The sampling technique using purposive sampling and sample determination based on after calculated based on Slovin formula amounted to 32 samples. So the number of questionnaires distributed in this study are as many as 32 questionnaires. While the method of analysis used in this study is multiple regression analysis with the help of SPSS program version 22.The results showed that justice and tax rates have an effect on tax evasion, while technology and information, discrimination, and taxation system do not influence tax evasion. Coefficient of determination by the five variables in this study affect the dependent variable of 60.3% while 39.7% influenced by other variables not described in this study. Future research is expected to use other variables or add another independent variable that may affect tax evasion.Keywords : Justice, Tax Rates, Technology and Information, Discrimination, Taxation System, and Tax Evasion.